TOI-969: a late-K dwarf with a hot mini-Neptune in the desert and an eccentric cold Jupiter - Lillo Box, J. (2023)
Context. The current architecture of a given multi-planetary system is a key fingerprint of its past formation and dynamical evolution history. Long-term follow-up observations are key to complete their picture. Aims. In this paper we focus on the confirmation and characterization of the components of the TOI-969 planetary system, where TESS detected a Neptune-size planet candidate in a very close-in orbit around a late K-dwarf star. Methods. We use a set of precise radial velocity observations from HARPS, PFS and CORALIE instruments covering more than two years in combination with the TESS photometric light curve and other ground-based follow-up observations to confirm and characterize the components of this planetary system. Results. We find that TOI-969 b is a transiting close-in (Pb ∼ 1.82 days) mini-Neptune planet (mb = 9.1 +1.1 −1.0 M⊕, Rb = 2.765+0.088 −0.097 R⊕), thus placing it on the lower boundary of the hot-Neptune desert (Teq,b = 941 ± 31 K). The analysis of its internal structure shows that TOI-969 b is a volatile-rich planet, suggesting it underwent an inward migration. The radial velocity model also favors the presence of a second massive body in the system, TOI-969 c, with a long period of Pc = 1700+290 −280 days and a minimum mass of mc sin ic = 11.3 +1.1 −0.9 MJup, and with a highly-eccentric orbit of ec = 0.628+0.043 −0.036. Conclusions. The TOI-969 planetary system is one of the few around K-dwarfs known to have this extended configuration going from a very close-in planet to a wide-separation gaseous giant. TOI-969 b has a transmission spectroscopy metric of 93, and it orbits a moderately bright (G = 11.3 mag) star, thus becoming an excellent target for atmospheric studies. The architecture of this planetary system can also provide valuable information about migration and formation of planetary systems.